Characterization of a novel HLA‐DRB1*07 allele, DRB1*07:83. (21st February 2018) - Balas, A.; Alenda, R.; Moreno‐Hidalgo, M. A.; García‐Sánchez, F.; Vicario, J. L.
Abstract : A new DRB1*07 allele, DRB1*07:83, was described in a Caucasian Spanish donor.